Impact of the economic, social and political context of Venezuela on the university teacher. Analysis from the Maslow’s Pyramid (Dissertare, 2020)
The complex economic, social and political reality of Venezuela in the second decade of the 21st century has significantly impacted the academic function of professionals in university education, obstructing optimal performance for teaching, research and extension functions. In this sense, the purpose of this research article is to interpret the impact of the socio-political and economic context of Venezuela on university teachers, taking into account the hierarchy of human requirements circumscribed in Maslow's pyramid. The methodology adopted in the research was framed in the documentary design, with a qualitative approach. The findings put Venezuela as the fourth country in the world in a situation of hunger, a context in which university teachers fail to satisfactorily cover their basic needs, even at the survival level. In this context, the study concludes as a priority to guarantee the human rights to the professionals of the university education in Venezuela, the satisfaction of their conative needs and the prevention of psychoneurotic-nutritional pathologies, to guarantee the performance of their academic functions.
Keywords: Maslow's Pyramid; university teaching; conative needs; humanitarian crisis; socio-political and economic context of Venezuela